Viruses isolated from cells persistently infected with vesicular stomatitis virus show altered interactions with defective interfering particles. - Horodyski, F M (1980)
Virus mutants isolated from persistent infections of vesicular stomatitis virus in BHK-21 cells were much less susceptible to interference mediated by the defective interfering particle used to establish the persistent infection. This mutational change occurred as early as 34 days in the persistent infection and continued for over 5 years. The earliest variants showed no oligonucleotide map changes and no difference in the temperature-sensitive phenotype from the original virus, but the later variants exhibited extensive map changes. These results suggest a possible role for defective interfering particles in the selection of the mutants.